Determinanty generowania kredytów gospodarczych w okresie pokryzysowym na przykładzie polskiego sektora banków spółdzielczych - Kil, Krzysztof; Miklaszewska, Ewa (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The post-crisis period stressed the role of small, local banks in corporatelending, particularly for SME, due to such their advantages as being based onrelationship banking and extensive knowledge of local market. However, it isstill unclear whether it is a short or long-term advantage. The aim of this paper isto analyze the factors affecting the size and quality of the loan portfolios of thePolish cooperative banks. In the empirical part, the study is based on statisticaldata and panel research, based on individual balance sheet data for the banksaffiliated to the BPS SA. The results confirm that the role of cooperative banksin lending to businesses increases, but also pointed to internal diversity of thesector in this area: growth in loans to the corporate sector was particularly strongfor large banks with strong capital, but also resulted in their declining safety andincreasing bad loans portfolio.